The Effect of Reading Interest and Vocabulary Mastery on Students’ Ability to Comprehend Narrative Text at State Senior High Schools in Cirebon - Siti Juaeriah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
The present study was conducted to respond to the students’ low ability to comprehend narrative text. This was likely due to their lack of reading interest and vocabulary mastery. Therefore, the study was aimed to find out the effect of reading interest and vocabulary mastery collectively on the ability of comprehending narrative text. The research question, then, formulated as: How can the students’ lack of reading interest and vocabulary mastery affect their ability to comprehend narrative text? Students’ reading interest in Indonesia is very low. This is because students today still ignore the importance of reading. The low reading interest in Indonesia are caused by various factors, such as environment, online game, and social media. Students’ vocabulary mastery in reading will affect their ability in comprehending and understanding the writer’s message through the writer’s writing. The research design used was classroom action. The subjects were first-year level students from state senior high school of 2, 3 and 4 Cirebon. The research method used was multiple regression technique. Questionnaires were administered to 60 participants. As a sample, the research used proportional random sampling technique. The data were collected using a questionnaire and a quiz then analyzed statistically using descriptive statistics such as mean, median, standard deviation, and standard inferential. It was aimed to find correlation coefficient with t testing using SPSS 20. The result of the implementation showed that: (1) there was a significant effect of both reading interest and vocabulary mastery on students’ ability to comprehend narrative text at state senior high schools in Cirebon. It was showed by the point of Sig = 0.000 < 0.05 and Fcount = 14.928. (2). There was a significant effect of reading interest on students’ ability to comprehend narrative text at state senior high schools in Cirebon. It was showed by the point of Sig = 0.005 < 0.05 and tcount = 2.932. (3). There was a significant effect of vocabulary mastery on students’ ability to comprehend narrative text at senior high schools in Cirebon. It was showed by the point of Sig = 0.033 < 0.05 and tcount = 2.181. Keywords: reading interest; vocabulary mastery; narrative text